1983
DOI: 10.1128/aac.23.5.793
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibilities of Coagulase-Negative Staphylococci Isolated from Urinary Infections

Abstract: The susceptibilities of 107 urinary isolates of coagulase-negative staphylococci to 19 antibiotics was determined by an agar dilution technique. Major differences in the antimicrobial susceptibilities of species of coagulase-negative staphylococci were observed. Staphylococcus epidermidis was more resistant to a wider spectrum of antibiotics than was Staphylococcus saprophyticus .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1984
1984
1989
1989

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…saprophyticus have yielded inconsistent and methoddependent results (15,20,27,44), these organisms had a unimodal distribution of penicillin G MICs (5,15,33,39). Based on our studies, we concluded that all strains either were ,-lactamase negative or produced ineffective enzyme and were susceptible to penicillin G; application of S. aureus MIC criteria was not appropriate to S. saprophyticus.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…saprophyticus have yielded inconsistent and methoddependent results (15,20,27,44), these organisms had a unimodal distribution of penicillin G MICs (5,15,33,39). Based on our studies, we concluded that all strains either were ,-lactamase negative or produced ineffective enzyme and were susceptible to penicillin G; application of S. aureus MIC criteria was not appropriate to S. saprophyticus.…”
Section: Discussionmentioning
confidence: 90%
“…saprophyticus is unique among staphylococci because it causes community-acquired bacteriuria in healthy young females and is susceptible to most antimicrobial agents; other species of coagulase-negative staphylococci are more likely to cause serious nosocomial infections and to be resistant to multiple antimicrobial agents (3,5,15,33,39).…”
Section: Discussionmentioning
confidence: 99%
“…Mean concentrations detected in atrial appendages up to 4 h after the beginning of infusion reached values 12 times the MIC for methicillin-resistant Staphylococcus aureus (14) and Staphylococcus epidermidis (20). Maximum levels of cefamandole and cloxacillin in atrial appendages were respectively one to five times and four to eight times the MICs of those antibiotics against these pathogens (5,14,19). The three antibiotics reached concentrations in heart tissue well above the respective MICs of penicillinase-producing and -nonproducing S. aureus (4,8,10).…”
Section: Discussionmentioning
confidence: 87%
“…For cefamandole tryptic soy agar (Difco) was the medium used, and Bacillus subtilis (Difco) was the indicator organism. For cloxacillin the same medium was inoculated with Sarcina lutea ATCC 9341 (5 ml of 18-h culture per 100 ml of medium).fFor fusidic acid 1 liter of medium containing vitamin-free Casamino Acids (Difco), 15.0 g; yeast extract (Difco), 5.0 g; L-cysteine, 0.05 g; sodium chloride, 2.5 g; glucose, 1.0 g; and agar (Difco), 24.0 g at a pH of 6.0 was inoculated with 10 ml of an 18-h culture of Corynebacterium xerosis Leo FF-M (6). Plates were incubated overnight at 370C for cefamandole and fusidic acid assays and at 30°C for cloxacillin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation